Perception and Participation of Women in Conservation and Ecotourism of Bird Watching in Kwau and Syoubri Villages - Lince Baransano; Mega Atria; Ludia Wambrauw; Ezrom Batorinding; Charlie D. Heatubun (Postgraduate, University of Mataram, 2025)
Kwau and Syoubri Villages in the Arfak Mountains are areas with Bird watching ecotourism. Women in these villages are often involved in ecotourism activities. This study aims to find out the perception and participation of women and their roles in ecotourism and conservation in Kwau and Syoubri Villages, as well as to find out the local knowledge and forms of activities and their application. The research was done in October–November 2023 in Kwau and Syoubri Villages, Manokwari Regency. The respondents were 40 women from each Kwau and Syoubri villages. Data was collected by filling out questionnaires and interviews, then the data was analyzed qualitatively and presented in the form of descriptive statistics. The measurement uses the Likert Scale method and participation rate. Women of Kwau and Syoubri Villages have a very good perception of Birdwatching, ecotourism, and conservation efforts. In the development and management of ecotourism and conservation, women in Kwau Village have a better perception than women in Syoubri Village, who have a neutral perception. The level of female participation in Kwau and Syoubri Villages is low. Women in Kwau Village have participated in the therapy stage such as running programs that support ecotourism and conservation activities. The participation rate of women in Syoubri Village at the manipulation stage is only listening to ecotourism programs and activities, but not being involved, and only partially at the therapy stage. Ecotourism management in Kwau Village is carried out based on the local communities, hence all communities benefit and participate at a certain stage. On the other hand, in Syoubri Village, it is only managed by individual ecotourism managers, and not all communities are involved. Therefore, most women are not directly involved. This research can contribute in terms of scientific information to strengthen ecotourism-based science learning and bird observation conservation